Cece Rios and the desert of souls - Rivera, Kaela (Harper, an imprint of HarperCollinsPublishers, 2021)
Privately questioning her remote community's superstitions about dangerous powerful spirits in their Devil's Alley home, Cecelia Rios experiments with the forbidden art of brujería to rescue her kidnapped sister.